Audio Visual Learning Media on Elementary School Students' Interest in Learning - Norfadila; Herwin; Nursakinah (Universitas Pendidikan Ganesha, 2024)
Learning media is a tool as an intermediary to facilitate classroom learning. The learning process using audio-visual learning media can make the learning process easier so that learning is more interesting and enjoyable. This research aims to analyze whether the application of audio-visual learning media to students' interest in learning in classes 5B and 5C can foster students' interest in learning. By using a quasi-experimental design and quantitative approach, this research is included in experimental research. The population in this study were all students in class 5B and 5C. Sampling in this study used a purposive sampling technique. The data collection method in this research is using a questionnaire, using and this research uses a Quasi experimental non-equivalent control group design or Quasi Experimental Design or usually called a quasi-experiment. The type of research used in this research is experimental research. Data analysis in this study used validity, normality and homogeneity tests as well as hypothesis testing which was carried out through the independent sample t-test. The research results show that the data has a normal and homogeneous distribution. There is a significant difference between the experimental class and the control class. Therefore, Ho is rejected and Ha is accepted. The average score in the experimental class was 61.22, while in the control class it was 58.46. Therefore, it can be concluded that audio-visual media has a significant influence on students' interest in learning.